IEEE 802.11e QoS provisioning at the MAC layer. - Yang Xiao (IEEE Wireless communications)
This article introduces the emerging IEEE 802.11e standard to support quality of service at the medium access control layer. Both the contention-based and contention-free centrally controlled channel access mechanisms are introduced by describing not only the MAC protocol operations and parameters, but also the call admission techniques and scheduling algorithm that have been designed for IEEE 802.11e. Finally, we provide simulation results aimed to highlight the capability of the EDCF to differentiate the traffic classes.